2021
DOI: 10.3390/nu13030783
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Efficacy of Calcium-Vitamin D Milk Fortification and Periodontal Therapy on Maternal Oral Health and Metabolic and Inflammatory Profile

Abstract: In this 2 × 2 factorial, outcome-assessor blinded, feasibility randomised trial we explored the effect of a non-pharmaceutical multi-component intervention on periodontal health and metabolic and inflammatory profiles among pregnant women with periodontitis receiving prenatal care in a Brazilian public health centre. 69 pregnant women (gestational age ≤20 weeks, T0) were randomly allocated into four groups: (1) fortified sachet (vitamin D and calcium) and powdered milk plus periodontal therapy during pregnancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…The authors reported no adverse effects; the intervention was acceptable, well tolerated, and feasible in the study population of low-risk pregnant women. The second study was a related trial that evaluated several combinations of calcium and vitamin D supplementation in milk, in addition to early (during pregnancy) vs late (after delivery) periodontal therapy [ 64 ]. The authors found no differences among groups regarding fortification; however, early periodontal therapy was associated with significantly less bleeding on probing.…”
Section: Sex Differences In Vitamin D and Calcium Supplementationmentioning
confidence: 99%
“…The authors reported no adverse effects; the intervention was acceptable, well tolerated, and feasible in the study population of low-risk pregnant women. The second study was a related trial that evaluated several combinations of calcium and vitamin D supplementation in milk, in addition to early (during pregnancy) vs late (after delivery) periodontal therapy [ 64 ]. The authors found no differences among groups regarding fortification; however, early periodontal therapy was associated with significantly less bleeding on probing.…”
Section: Sex Differences In Vitamin D and Calcium Supplementationmentioning
confidence: 99%
“…There is evidence that the inflammation due to gingivitis and/or periodontitis tends to worsen during pregnancy due to hormonal changes, and these have implications for maternal health beyond the oral cavity [ 5 ]. For example, this inflammation could lead to a low-grade systemic inflammatory and metabolic disturbances which can have an impact on pregnancy outcomes [ 5 ]. Therefore, there appears to be a relationship between periodontal inflammation and diabetes, and thus managing inflammatory periodontal diseases may improve glycaemic control and associated diabetic complications.…”
mentioning
confidence: 99%
“…Therefore, there appears to be a relationship between periodontal inflammation and diabetes, and thus managing inflammatory periodontal diseases may improve glycaemic control and associated diabetic complications. In recognition of this, Rodrigues Amorim Adegboye et al [ 5 ] conducted a randomised controlled trial to explore the effect of a non-pharmacological multi-component intervention on periodontal health and metabolic and inflammatory profiles among pregnant women with periodontitis. The study involved 69 pregnant women receiving prenatal care in a Brazilian public health centre who were randomly allocated to four groups: (1) fortified sachet (vitamin D and calcium) and powdered milk plus periodontal therapy during pregnancy (early PT), (2) placebo sachet and powdered milk plus early PT, (3) fortified sachet and powdered milk plus late PT (after delivery), and (4) placebo sachet and powdered milk plus late PT [ 5 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations